KETERKAITAN KETERSEDIAAN UNSUR HARA Ca, Mg, DAN Na DENGAN PRODUKSI DAN MUTU TEMBAKAU KEMLOKO DI KABUPATEN TEMANGGUNG, JAWA TENGAH - Anita Dwy Fitria; S Sudarto; D Djajadi (Jurnal Tanah dan Sumberdaya Lahan, 2018)
Temanggung is known as best quality tobacco producer. The potential production of Temanggung tobacco ranges from 900 to 1200 kg ha-1, but the present tobacco production is still low at 703 kg ha-1. The type of tobacco that is widely cultivated in Temanggung is Kemloko tobacco, which is known as the best local tobacco variety. This study was aimed to explore the relationship of Ca, Mg and Na availability for production and quality of Kemloko Tobacco in Temanggung Regency, Central Java. Soil samples were collected from field at 0-20 cm depth. The chemical analysis results showed that the distribution of Ca availability was low to high (2-20 me 100 g-1), availability of Mg was high to very high (2.1 to> 8 me 100 g-1), availability of Na was low to medium (0.1-0.4 me 100 g-1). The results of correlation analysis were as flows: Ca and production was 0.1520, Ca and quality index was 0.0660, Mg and production was -0.0676, Mg with quality index was (-0.0419), Na and production was -0.2304, Na and quality index was -0.1023. All correlation coefficients were weak. The average yield of moderate tobacco production was 311-609 kg ha-1 with the result of the average quality index entering into the very low class of 20-48.